An outcome-based assessment process for accrediting computing programmes. (2nd November 2017) - Harmanani, Haidar M.
ABSTRACT: The calls for accountability in higher education have made outcome-based assessment a key accreditation component. Accreditation remains a well-regarded seal of approval on college quality, and requires the programme to set clear, appropriate, and measurable goals and courses to attain them. Furthermore, programmes must demonstrate that responsibilities associated with the goals are being carried out. Assessment leaders face various challenges including process design and implementation, faculty buy-in, and resources availability . This paper presents an outcome-based assessment approach that facilitates faculty participation while simplifying the assessment and reporting processes through effective and meaningful visualisation . The proposed approach has been implemented and used for the successful ABET accreditation of a computer science programme, and can be easily adapted to any higher education programme.